Music Creativity In The Brascong Vijaya Kusuma Keroncong (Universitas Negeri Semarang, 2022)
Creativity in music can be formed by observing, studying, and understanding existing creative works or creating new music. In the city of Salatiga, there is a keroncong orchestra called